2018
DOI: 10.3390/su10030760
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Regulatory Focus on Individuals’ Donation Behavior

Abstract: Abstract:We examine how individuals' regulatory focus affects their donation behavior and how personal events experienced before the donation moderate this relationship. In this research, regulatory focus refers to the basic motivational orientation that affects how individuals pursue their goals. We propose that donors will judge potential rewards and risks associated with making a donation when deciding whether to donate and that regulatory focus and personal events will have a significant influence on this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(76 reference statements)
0
13
0
Order By: Relevance
“…Ramanathan and Dhar (2010) found that promotion-focus consumers are more sensitive to sales promotion message like “save $ x,” but prevention-focus consumers are more sensitive to sales promotion message like “get $ x off.” Even though this branch of research produced important findings, they also mentioned there is little information on the effects of regulatory fit on people’s reactions and value assignment (Higgins, 2000; Lockwood et al , 2002; Avnet and Higgins, 2006). A number of research tested regulatory focus and fit’s effect on many decision-making and behavioral situations including online information sharing and online purchase (Hsu et al , 2017; Georgiana, 2018), individual’s donation (Park and Ryu, 2018) and team performance (Park et al , 2015; Lai et al , 2018). Hsu et al ’s (2017) research indicated that regulatory fit has a more significant effect on online consumers’ purchase intention than the non-fit condition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ramanathan and Dhar (2010) found that promotion-focus consumers are more sensitive to sales promotion message like “save $ x,” but prevention-focus consumers are more sensitive to sales promotion message like “get $ x off.” Even though this branch of research produced important findings, they also mentioned there is little information on the effects of regulatory fit on people’s reactions and value assignment (Higgins, 2000; Lockwood et al , 2002; Avnet and Higgins, 2006). A number of research tested regulatory focus and fit’s effect on many decision-making and behavioral situations including online information sharing and online purchase (Hsu et al , 2017; Georgiana, 2018), individual’s donation (Park and Ryu, 2018) and team performance (Park et al , 2015; Lai et al , 2018). Hsu et al ’s (2017) research indicated that regulatory fit has a more significant effect on online consumers’ purchase intention than the non-fit condition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, this article attempts to introduce motivation into the research model to explore what kind of motivation plays an intermediary role between innovative resources and responsible innovation. In addition, the regulation focus theory has important applications in the study of corporate behavior motivation [14]. The regulatory focus theory divides the basic motivation of enterprises into two types: the promotion focus and the prevention focus.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the fundamental drivers of human behaviors, this research employs regulatory focus, commonly used in marketing literature such as donation behavior [26], perception of advertisement [27] and eco-behavior [28]. Especially, socially excluded people differently developed motivations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%